Content Analysis of Nationalism Character Education in Wonogiri Folklore as An Elementary School Literacy Media - Aprin Wahyani; Fitri Puji Rahmawati; Yeny Prastiwi; Laili Etika Rahmawati; Ali Imron Al Ma’ruf (Journal of Innovation in Educational and Cultural Research, 2022)
Instilling the character of nationalism in students can be done through literacy programs with folklore media. Therefore, it is necessary to analyze the content of character education in folklore. The purpose of this study was to describe the content of nationalism character education in folklore from Wonogiri (Central Java) as a literacy medium for elementary school students. This research is a qualitative descriptive study with a content analysis model. The results of the analysis found that the main values of the character of nationalism include: (1) respecting, maintaining, and appreciating the diversity of cultures and ethnic groups, (2) discipline and obeying the law, (3) protecting the environment, (4) love for the homeland, (5) Achieve and excel, (6) Willing to sacrifice. The conclusion of the study shows that not all the main values of the character of nationalism are contained in every folklore, therefore teachers as literacy implementers must be able to add these deficiencies from other sources so that they can contribute to inculcating the character of nationalism in students.Â